2000
DOI: 10.1021/om990840q
|View full text |Cite
|
Sign up to set email alerts
|

Protonolysis of Dimethylplatinum(II) Complexes:  Primary Attack at Metal or Ligand

Abstract: The complexes [PtMe 2 (DMEP)], 1, and [PtMe 2 (DMPP)], 2 [DMEP, DMPP ) Me 2 N(CH 2 ) n Nd CH-2-C 5 H 4 N, n ) 2, 3, respectively], contain ligands that chelate to platinum through the imine and pyridyl groups, with the tertiary amine group not coordinated. Methyl iodide reacted with complex 1 to give [PtIMe 3 (DMEP)] but reacted with 2 to give a mixture of [PtIMe 3 (DMPP)] and [PtMe 3 (DMPP)]I, indicating the greater ability of DMPP to act as a fac-tridentate ligand. Complex 2 reacted with MeO 3 SCF 3 to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 33 publications
4
22
0
Order By: Relevance
“…Crystallographic data are given in Table 1 3 and selected bond distances and angles shown in Table 2. The nitrogen-platinum bonds of 1.996(3) Å (pyridine) and 1.985(3) Å (imine) are similar to those reported in other iminopyridine platinum systems (34)(35)(36). Slightly longer Pt-N bond distances are observed in related five-coordinate Pt(II) (37,38) and Pt(IV) complexes (39).…”
Section: Resultssupporting
confidence: 79%
“…Crystallographic data are given in Table 1 3 and selected bond distances and angles shown in Table 2. The nitrogen-platinum bonds of 1.996(3) Å (pyridine) and 1.985(3) Å (imine) are similar to those reported in other iminopyridine platinum systems (34)(35)(36). Slightly longer Pt-N bond distances are observed in related five-coordinate Pt(II) (37,38) and Pt(IV) complexes (39).…”
Section: Resultssupporting
confidence: 79%
“…3). The nitrogen-platinum bonds of 2.017(5) Å (pyridine) and 1.997(5) Å (imine) are similar to those reported in other iminopyridine platinum systems [10,[22][23][24]. The imine C(6)-N(7) distance is 1.286(8) Å and is in the range of accepted carbon-nitrogen double bonds [25].…”
Section: Crystal Structuressupporting
confidence: 73%
“…66,67 Other studies also observed hydridoalkylplatinum(IV) species during low-temperature protonation. [68][69][70][71][72] This lead to the assumption of an oxidative addition mechanism of an alkane to the metal, presumably from a 75 With bulky substituent in the ortho position of the diimine ligand, η 2 -benzene coordination appeared rate limiting while in the absence of ortho substituent, the C-H cleavage became the rate determining step. This was explained by steric destabilisation of both the intermediate π-benzene complex and the transition state by the ortho methyl group.…”
Section: Methodsmentioning
confidence: 99%